Unpleasant market experience and consumer complaint behavior - Mahmud Mahayudin, Nurzatul Hakimah; Haron, Sharifah Azizah; Chan, Benjamin Yin Fah (Canadian Center of Science and Education, 2010)
The 33% increase in number of complaints received by the National Consumer Complaint Centre (NCCC) in 2007 compared to previous year can mean two things: i) consumer are aware more of their rights or ii) the suppliers of goods and services perform worse in 2007. Unsatisfied consumer in either pre- or post consumption, complaint because of the unpleasant experiences in the consumption process or that the product perform below their expectation. The survey which utilized stratified random sampling with 61.7% of response rate was recorded. The objectives of the study are to analyze unpleasant experiences and complaint behavior among consumer. Findings indicated that respondents who are female, living in rural area and has higher level of assertiveness were more likely to encounter unpleasant experiences in marketplace. Further analysis indicated that, unpleasant experiences were mainly influenced by assertiveness rather than socio-demographics background or consumer knowledge.